2x-26=-38+23x

Simple and best practice solution for 2x-26=-38+23x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-26=-38+23x equation:


Simplifying
2x + -26 = -38 + 23x

Reorder the terms:
-26 + 2x = -38 + 23x

Solving
-26 + 2x = -38 + 23x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-23x' to each side of the equation.
-26 + 2x + -23x = -38 + 23x + -23x

Combine like terms: 2x + -23x = -21x
-26 + -21x = -38 + 23x + -23x

Combine like terms: 23x + -23x = 0
-26 + -21x = -38 + 0
-26 + -21x = -38

Add '26' to each side of the equation.
-26 + 26 + -21x = -38 + 26

Combine like terms: -26 + 26 = 0
0 + -21x = -38 + 26
-21x = -38 + 26

Combine like terms: -38 + 26 = -12
-21x = -12

Divide each side by '-21'.
x = 0.5714285714

Simplifying
x = 0.5714285714

See similar equations:

| 16t^2-8t-15=0 | | 4x+7-3x=11 | | x=-3+-1.5Y | | 2x^2+16x+23=0 | | 4t-(5+2t)=37 | | 3x+5y=24 | | 6w+2w=25+47 | | 5(4x+7)-3(5-2x)=98 | | 3x-15=3(x-5) | | x^4=144 | | x-6=-3+9 | | 10-8x=91-29x | | (3x+4)(5x+8)= | | 2x+8+4x-3= | | (4+6)(2+4x)=45-2.5(x+3) | | -6(5-2n)=-6 | | .5b=58 | | y^2+9y+54=0 | | 0=2x^3-x^2-13x-6 | | 5+3(n-4)=2(n+1) | | 8p-5+4=23 | | x^2-5x-2= | | 3y+9x=15 | | -5-3n+6n=-11 | | y=24 | | s*4+8=20 | | (7x^3-8x^2+4)-(2x-7x-8)= | | -21x+7=7x | | 13h+6d-9d-7h= | | (7x^3-9x^2+4)-(2x^3-7x-8)= | | 124-6x=21x+22 | | (2xy^2-5)+(7xy^2+8)= |

Equations solver categories